Summaries of Judgments, Advisory Opinions and Orders of the International Court of Justice 2013-2017 - United Nations (United Nations, 2018)
This publication contains summaries of the judgments, advisory opinions and orders of a substantive nature issued by the International Court of Justice, the principal judicial organ of the United Nations, from 1 January 2013 to 31 December 2017. It is the continuation of five earlier volumes on the same subject (ST/LEG/SER.F/1 and Addenda 1, 2, 3 and 5), which covered the periods 1948–1991, 1992–1996, 1997–2002, 2003–2007 and 2008–2012, respectively. During the period covered by this publication, the Court issued 28 judgments, advisory opinions and orders of a substantive nature. It should be noted that the materials contained herein are summaries prepared by the Registry of the Court, which do not involve the responsibilities of the Court itself.